New resinicolous Chaenothecopsis species from China - Tuovila H; Davey ML; Yan LH; Huhtinen S; Rikkinen J (ALLEN PRESS INC, 2022)
Four new resinicolous species of Chaenothecopsis are described from China: Chaenothecopsis perforata from exudate of Rhus chinensis (Anacardiaceae), C. pallida from exudate of Ailanthus altissima (Simaroubaceae), C. resinophila from exudate of Kalopanax septemlobus (Araliaceae) and C. hunanensis from resin of Pinus massoniana (Pinaceae). All the new species are compared with previously described resinicolous mycocalicioid taxa, and several new features in these species are presented. The newly described species cannot always be distinguished by any single character, but they all possess unique combinations of morphological, chemical and ecological features. Several aspects in the ecology and evolution of boreal and tropical resinicolous species are briefly discussed.